Walkability indices and children's walking behavior in rural vs. urban areas. (November 2021) - Bucko, Agnes G.; Porter, Dwayne E.; Saunders, Ruth; Shirley, Lynn; Dowda, Marsha; Pate, Russell R.
Abstract: Purpose: This study described associations between selected walk indices (WI) and walking and physical activity behaviors in rural and urban children. Findings: WI were higher in urban environments, yet children from rural areas walked for transportation more than children from urban areas. There was a negative correlation between National WI scores and walking for transportation in urban areas, and between the Frank WI scores and walking for exercise in rural areas. Conclusions: Indices of walkability are not associated with objectively measured physical activity or self-reported walking behavior in children living in rural and urban settings. Highlights: Walkability scores were lower in rural compared to urban environments. Children living in urban and rural areas did not differ in walking behavior. Physical activity did not differ between children living in urban vs. rural areas. Only small, negative correlations existed between walkability and walking behavior. Walkability was not correlated with physical activity levels in children.